Investment fund portfolio selection strategy - Kucko, Irena (Business: Theory and Practice, 2007)
The paper is based on the proceedings of the International Conference ‘Business and Management 2006’. The problems of investment fund portfolio selection are discussed further and deeper, though the problem solved differs by covered period, selected stocks, and the principles of stock selection. The research scheme is supplemented with a new step, now the stocks are selected not accidentally as in previous study, but are classified and categorized according to certain variables. Asset management is of the strategic importance for investment funds industry. By allocating savings to productive investment the asset management industry is the key for the overall functioning and development of the Lithuanian economy. Financial innovations, changes in investors’ needs and preferences, and industry restructuring are transforming financial markets. In the investment funds industry the main driver of change is product engineering. The paper presents investment fund portfolio selection strategy and the results of its application, seeking for maximal gain in the Lithuanian capital market according to the scheme of weekly portfolio rebalancing. The strategy has been applied to stocks of Vilnius Stock Exchange.